P7 - Green Flow Nitration of Bacterial Cellulose.pdf - Gill, Philip (Cranfield University, 2023)
Green Flow Nitration of Bacterial Cellulose B, Nicol., Dr I, Wilson., Dr J-F, Pons. - Cranfield University 9th International Nitrocellulose Symposium - Poster
Keywords: 'nitrocellulose'